Heteroepitaxial growth and characterization of BiFeO3 thin films on GaAs. (27th October 2016) - Rahman, Md Shafiqur; Ghose, Susmita; Gatabi, Javad R; Rojas-Ramirez, Juan S; Pandey, R K; Droopad, Ravi
Abstract: The paper deals with the integration of well-known bismuth ferrite (BiFeO3 ) multiferroic oxide with GaAs semiconductor. First 5 nm ultrathin SrTiO3 films were grown on GaAs (001) substrates as an intermediate buffer layer by molecular beam epitaxy. Then, room temperature multiferroic BiFeO3 (BFO) thin films were deposited by pulsed laser deposition. X-ray diffraction measurement showed high quality epitaxial BFO films with pure (00l) orientation. The dielectric loss has been effectively suppressed and the saturated polarization–voltage ( P – V ) hysteresis loops were obtained. The ferroelectric domains switching was affirmed by piezo-response force microscopic studies. A large remnant polarization P r (∼80 μ C cm −2 ) combined with the enhanced magnetization (72 emu cm –3 ) at 300 K was achieved for the optimal growth conditions. The optical properties were measured using the ellipsometry technique for the BFO thin films. The thickness and optical constants of the BFO films were obtained by taking into consideration the dielectric parameters as described by the Tauc-Lorentz model. Finally, direct bandgap was estimated at 2.70 eV which is highly comparable to BFO films grown on different substrates.